Archives internationales de pharmacodynamie et de thérapie. - Heymans Institute of Pharmacology (Gand [Belgium] : H. Engelcke ; Paris : O. Doin, 1899)
"International archives of pharmacology."
Chemical abstracts
Supplements accompany some issues.
Predominantly in English, French, and German.
Issued by: Heymans Institute of Pharmacology, <1970>-1996.
Description based on: Vol. 195, no. 1 (Jan. 1972); title from cover.
Keywords: Pharmacology -- Periodicals; Pharmacology; Farmacodynamica; Drug Therapy; Pharmacology; Periodicals; Periodicals; Periodical